FROM EXPORTER TO IMPORTER: TRACING THE SHIFTING DYNAMICS OF INDONESIA’S OIL TRADE PERIOD 2001-2022 - Priyadani, Muhammad Syahputra; Sri Setiawati, Ririt Iriani (Universitas 17 Agustus 1945 Surabaya, 2025)
This study investigates the shifting dynamics of Indonesia’s oil trade by analyzing the influence of domestic crude oil production, global oil prices, and the USD–IDR exchange rate on Indonesia’s crude oil import volume from 2001 to 2022. Despite numerous national energy policies aimed at achieving self-sufficiency, Indonesia remains heavily dependent on oil imports due to its limited refining capacity. Using annual time-series data and multiple linear regression analysis, supported by classical assumption tests to ensure model validity, the results show that both domestic production and oil prices have a statistically significant positive effect on imports. This suggests that increasing domestic production does not necessarily reduce import dependency, largely due to the structural limitations of Indonesia’s oil refining infrastructure. In contrast, the exchange rate exerts a significant negative effect, indicating that Rupiah depreciation curbs imports by raising import costs. The model accounts for 82% of the variation in oil import volumes, emphasizing the strategic importance of these macroeconomic variables. By isolating only three key factors (production, price, and exchange rate) this study offers a focused empirical framework for understanding oil import behavior. The findings highlight the need to accelerate domestic refinery development, implement hedging mechanisms against currency volatility, and design responsive policy tools to global oil price shifts, thereby reducing import reliance and strengthening national energy security.